ANALISIS SISTEM PENGENDALIAN BERKAS REKAM MEDIS DI RUMAH SAKIT UNIVERSITAS AIRLANGGA SURABAYA - Septiya Atik Cahyani; Andri Permana Wicaksono; Novita Nuraini (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Medical record controlling is the supervision of medical record borrowing and medical record returning to thestorage rack. Based on observation at Airlangga University Hospital in October 2019 there were 3 out of 5borrowed files were returned by exceeding the deadline. From December 2019 until February 2020 therewere 11 of the 16 medical record files borrowed by other units, but the expedition book did not contain anyinformation regarding the date of returning file. Delay in the medical record returning file results in misplacedor miss file. From March 9th, 2020 to March 13th, 2020 there were 237 of 3053 medical record files thatwere misplaced or miss file. This study aimed to analyze the medical record file control system at AirlanggaUniversity Hospital using the 5M method (man, method, machine, material, and money). This research wasqualitative. Data collection techniques used were observation, interviews, and documentation. The subjectof study was medical record officer. The results show that the factors causing problems in controlling medicalrecord files are high workload of officers, late return of medical record files, officer discipline in usingexpedition books, absence of tracers as a substitute for medical record files, and the number of storageshelves that were under the needs. Suggestions for the problems are to add more officers in the fillingsection, conduct socialization and evaluate officers in using expedition books, make electronic tracerapplications, and adding storage shelves.